The little gardener : helping children connect with the natural world - Cerny, Julie A. (Princeton Architectural Press, 2020)
The Little Gardener is an engaging illustrated guide for parents, grandparents, caregivers, and educators who want to help children explore the natural world through gardening. Part how-to, part teaching tool, and part inspiration, The Little Gardener is a thoughtful combination of detailed instructions, tips, anecdotes, and seasonal activities designed to connect gardeners to natural systems. With fun projects, useful charts, and creative journal prompts, The Little Gardener shows gardeners of all ages how to envision and build their garden together by making the process an adventure to be treasured, with much to learn along the way.